Kepatuhan Hukum Indonesia terhadap Pelaksanaan Chemical Weapons Convention dalam Memitigasi Ancaman Terorisme Berbasis Senjata Kimia - Jaka Triyana, Heribertus; Prasetiyo, Putri Widhyastiti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 3 (2024)DO - 10.24843/JMHU.2024.v13.i03.p09, 2024)
This research aims to critically examine the institutionalization of the Chemical Weapons Convention (the Convention) particularly for its effective implementation, coordination, and procedure among institutions since Indonesia ratified in 1998. It has significance since Indonesia is very prone to imminent threats of chemical terrorism attacks due to its geographical features, openness of information technology, and religious sentiments. This research is conducted by normative legal research revealing secondary data on who have authorities and how they carry out legal obligations determined by the Convention in Indonesia in terms of institutionalization, coordination, preventive procedures, and punishment. In this regard, clarity and robust institutionalization as mandated by the Convention are two determining elements perceived as peremptory norms that should be observed. It reveals that national institutionalization needs to be improved by increasing public participation in order to know who are the leading ministries and institutions to detect, protect and anticipate chemical terrorism in Indonesia as well as legitimate aims, authorities, and allocation of available resources. At the same time, the public shall be disseminated by relevant information regarding policies, programs, and actions on how they react to chemical terrorism threats in order to mitigate risks and lack of resources once they deal with such imminent threats.